If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(j + 434) = 984 Reorder the terms: 6(434 + j) = 984 (434 * 6 + j * 6) = 984 (2604 + 6j) = 984 Solving 2604 + 6j = 984 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2604' to each side of the equation. 2604 + -2604 + 6j = 984 + -2604 Combine like terms: 2604 + -2604 = 0 0 + 6j = 984 + -2604 6j = 984 + -2604 Combine like terms: 984 + -2604 = -1620 6j = -1620 Divide each side by '6'. j = -270 Simplifying j = -270
| x^2+5x+5x+24=0 | | (3x-5)x=0 | | 19(r+954)=266 | | y=26-4*6 | | y=26-4*5 | | x+8=1008 | | r^2+10r+35=0 | | y=26-4*4 | | 7x-9=7(x-1)-2 | | 20/14=90/t | | y=26-4*2 | | T^2=4t+6 | | y=26-42 | | y-12=2x^2+8x+8 | | 19b-(-29)=352 | | 2x+14=5+2x+(x+3) | | x*2+14=5+2x+(x+3) | | 3+5u=-32 | | 11+r=9x-4 | | x+21=5+2x+(x+3) | | 6x^2-12x-33=3 | | -12=2v-4 | | 9(k+4)=81 | | x*7=5+2x+(x+3) | | 2/5(10x-10y)-3/4(12x-24y)= | | 6*7=5+2x+(x+3) | | 72=2(t-26) | | 6x-10=2x+5+3(x-5) | | 4X-y=-27 | | 100x^2+2100x-10000=0 | | 9x^2-18n-16=0 | | -9z-9=2z-10 |